The clinical relevance of humoral immune responses to Globo H-KLH vaccine adagloxad simolenin (OBI-822)/OBI-821 and expression of Globo H in metastatic breast cancer. Issue 6 (22nd June 2022) - Hung, Jung-Tung; Chen, I-Ju; Ueng, Shir-Hwa; Huang, Chiun-Sheng; Chen, Shin-Cheh; Chen, Mu-Yi; Lin, Yung-Chang; Lin, Chun-Yen; Campbell, Michael J; Rugo, Hope S; Yu, Alice L
Abstract : An international randomized phase II trial of Globo H (GH) vaccine, adagloxad simolenin/OBI-821 in 349 patients with metastatic breast cancer showed longer progression-free survival (PFS) in vaccinated patients who developed anti-Globo H (anti-GH) IgG than those who did not and the placebo group. The impacts of anti-GH IgM and GH expression on peak anti-GH IgG and clinical outcome were further evaluated. The titers of anti-GH IgG and IgM were determined by ELISA. GH expression in tumor was examined by immunohistochemical staining. Immunophenotyping was conducted by flow cytometry. Adagloxad simolenin elicited anti-GH IgM which peaked at titers ≥1:80 between weeks 5 and 13. The mean anti-GH IgG titer peaked at week 41 and decreased thereafter on the completion of vaccination. One log increase in peak IgM was associated with 10.6% decrease in the HR of disease progression (HR: 0.894, 95% CI: 0.833 to 0.960, p=0.0019). Patients with anti-GH IgM ≥1:320 within first 4 weeks after vaccination had significantly higher maximum anti-GH IgM (p<0.0001) and IgG titers (p<0.0001) than those with <1:320. Moreover, the median PFS appears to be longer for patients with anti-GH IgM ≥1:320 within first 4 weeks than those with anti-GH IgM titer <1:320 (11.1 vs 7.3 months, p=0.164), but not statistically significant. Among patients with H score ≥80 for GH expression by immunohistochemistry, the vaccination group (n=42) seemed to have better PFS than the placebo group (n=23) (HR=0.59; 95% CI: 0.32 to 1.10, p=0.10), but the difference did not reach statistical significance. In addition, peak levels of anti-GH IgM were higher in patients who had lower percentage of activated regulatory T cells (Treg cells; CD4 + CD45RA - Foxp3 high ) at baseline than those who had higher activated Treg cells (p=0.042). This study demonstrates that adagloxad simolenin induced both IgG and IgM antibodies against GH. Anti-GH IgM ≥1:320 within first 4 weeks or low activated Treg cells at baseline may help to select patients who are likely to produce a higher level of GH-specific IgM and IgG in the future.